2021
DOI: 10.1177/10778012211034217
|View full text |Cite
|
Sign up to set email alerts
|

Communicating a History of Sexual Trauma: Partner Responses to Women's Disclosure

Abstract: The study aimed to understand how women who experienced sexual trauma but are now in a healthy relationship perceive their partners’ responses to their disclosure of sexual trauma. Forty-one women completed an in-depth semi-structured phone interview. Responses were analyzed using reflexive thematic analysis, identifying two overarching themes and six subthemes. The results provide a voice to the needs and preferences of women who experienced sexual trauma, but are navigating communication in a healthy relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Muffly and Gerney (2015) investigated occupational preferences and found that people having experienced sexual assault (contrary to controls and to people having experienced a car accident or mugging) avoided occupations involving interpersonal touch. Finally, a qualitative study suggested that many women victim of sexual IPV, when disclosing their past trauma to their new partner, consider it important that the partner respects their physical boundaries and highlights the need not to be touched at certain times (Lukacena & Mark, 2022). This underlines the importance for victims of IPV to control how and when they are touched in their new relationship.…”
Section: Ipv Trauma and Affectionate Touchmentioning
confidence: 99%
“…Muffly and Gerney (2015) investigated occupational preferences and found that people having experienced sexual assault (contrary to controls and to people having experienced a car accident or mugging) avoided occupations involving interpersonal touch. Finally, a qualitative study suggested that many women victim of sexual IPV, when disclosing their past trauma to their new partner, consider it important that the partner respects their physical boundaries and highlights the need not to be touched at certain times (Lukacena & Mark, 2022). This underlines the importance for victims of IPV to control how and when they are touched in their new relationship.…”
Section: Ipv Trauma and Affectionate Touchmentioning
confidence: 99%
“…Travmatik olayların olumsuz fiziksel sonuçların yanında travma sonrası stres bozukluğu (TSSB) (Brewin ve diğ., 2000;Larsen ve Pacella, 2016), depresyon (Laugharne, Lillee ve Janca, 2010), kaygı (Magnavita ve diğ., 2021), kendine zarar verme davranışı, intihar (Gilbert ve diğerleri, 2009), maddenin kötüye kullanımı ve/veya bağımlılığı (Enoch, 2011) gibi çeşitli psikolojik sonuçlara da neden olabilmektedir. Bununla birlikte travma deneyimi; yaşamın anlamının keşfedilmesi (Zeligman ve diğ., 2019), kaliteli yakın ilişkilerin gelişmesi (Lukacena ve Mark, 2021), psikolojik sağlamlığın gelişmesi ve travma sonrası büyüme (Brooks ve diğ., 2020;Michalchuk ve Martin, 2019) gibi bazı olumlu kazanımlarla da sonuçlanabilmektedir.…”
Section: Travma Ve Krizunclassified
“…Partners of survivors sometimes felt their needs were not being met and they experienced strain in the relationship following disclosure of sexual assault [ 25 ]. However, although disclosure of prior sexual trauma to a new partner is common, it isn’t always supportively received, and the reception of the disclosure may impact the extent to which the relationship experiences strain [ 32 ]. In another study, the results showed that partners were cautious about navigating sexual intimacy with the survivor and survivors reported that they sometimes got triggered by their partner or experienced dissolution of their relationship because of the impact of the assault on sexual functioning [ 25 ].…”
Section: Introductionmentioning
confidence: 99%